Surfactant-Assisted Synthesis of Pt Nanocubes Using Poly(N‑isopropylacrylamide) Nanogels - Watanabe, Jun; Tanaka, Yoshiaki; Maeda, Yuusuke; Harada, Yusuke; Hirokawa, Yoshitsugu; Kawakita, Hidetaka; Ohto, Keisuke; Morisada, Shintaro (Langmuir, 2021)
Poly(N-isopropylacrylamide) (PNIPAM) nanogels were prepared by emulsion polymerization using sodium dodecyl sulfate (SDS) and employed as a capping agent in platinum nanoparticle (Pt NP) synthesis by liquid-phase reduction with hydrogen gas. When the PNIPAM nanogels were used without removing SDS, that is, a slight amount of SDS was included in the reaction solution, Pt nanocubes (NCs) were predominantly produced (>80%). The proportion of the resultant Pt NCs was much higher than that obtained using the PNIPAM linear polymer (∼60%). To clarify the effects of the three-dimensional polymer network and SDS, we synthesized Pt NPs using the PNIPAM nanogel without SDS (SDS-free PNIPAM nanogel) and found that Pt NCs are rarely formed, and most NPs obtained have an irregular shape. When only SDS was used as a capping agent, NCs were hardly obtained, but other polyhedral NPs were formed. Furthermore, the use of SDS together with the PNIPAM polymer led to the decrease in the proportion of the Pt NCs compared with that obtained using only the linear polymer. These results indicate that the enhancement of the Pt NC proportion using the PNIPAM nanogel with SDS is attributable to not only the three-dimensional polymer network of the PNIPAM nanogel but also the assist of SDS as a capping agent.